The Effect Of Motivation, Discipline And Competency On Employee Satisfaction Bank BTN Medan - Cindy Milenia; Katherine; Hendry (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of motivation, discipline, and competency on employee satisfaction at Bank BTN Medan. This type of research is explanatory research. The population in this study were all employees who worked at Bank BTN as many as 385 employees. Due to the large number of population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are 196 respondents. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that motivation, discipline, and competency partially or simultaneously have a positive and significant effect on employee satisfaction at Bank BTN Medan. Based on the results of this study, the implications for management are to further improve motivation, improve a better discipline, update the competency.